2009
DOI: 10.3835/plantgenome.2009.07.0019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Profiling Established the Awn as the Major Photosynthetic Organ of the Barley Spike While the Lemma and the Palea Primarily Protect the Seed

Abstract: The lemma, palea, and awn of a barley (Hordeum vulgare L.) spike are photosynthetic organs that supply the developing seed with carbohydrates. The lemma and palea also enclose the seed and protect it from pathogens and insects. Despite the important roles they play, little information exists on gene expression in these organs that identifi es their function. In this study, we compared gene expression among the lemma, palea, awn, and developing seed of barley during grain fi lling using the Barley1 Genome Array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Previous studies have shown that the photosynthetic activity of the spike in general and the awn in particular are important for grain filling in barley (Abebe et al 2009; Bort et al 1994; Scharen et al 1983; Xue et al 1997). We have shown that de-awning Morex plants shortly after heading resulted in a significant reduction in seed width and TGW, suggesting that awn length significantly contributes to grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the photosynthetic activity of the spike in general and the awn in particular are important for grain filling in barley (Abebe et al 2009; Bort et al 1994; Scharen et al 1983; Xue et al 1997). We have shown that de-awning Morex plants shortly after heading resulted in a significant reduction in seed width and TGW, suggesting that awn length significantly contributes to grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Within the spike the awns are the main contributors to the photosynthetic activity (Abebe et al 2009). Consequently, the absence of awns reduces seed weight and size because of a reduction in starch content (Bort et al 1994; Grundbacher 1963; Jiang et al 2006; Li et al 2006; Scharen et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…This explains why rice awns are not photosynthetically active since they lack chlorenchyma [ 19 ]. Because awns are located at the top of the canopy where light is abundant, they are suitable for light interception and CO 2 uptake, so their photosynthetic role has been reported to be large and can account for as much as 90% of total spike photosynthesis in barley [ 20 ] and between 40–80% in wheat [ 5 ]. According to Evans et al [ 21 ], wheat awns can double the net assimilation rate for grain filling under well-watered regimes, and can contribute between 34–43% when the moisture supply is limited.…”
Section: Impact Of Awns On Grain Yield and Plant Biomassmentioning
confidence: 99%
“…Modern wheat cultivars seem to have a higher awn size and higher awn contribution to grain yield than older cultivars (Maydup et al ). In barley, the awn preferentially expressed genes for the non‐enzymatic and enzymatic removal of ROS in the chloroplasts; the predominant genes overexpressed in the awn for the enzymatic removal of ROS included the chloroplast Cu/Zn‐SOD, ascorbate peroxidase, thioredoxin reductase and monodehydroascorbate reductase; the non‐enzymatic antioxidants included ascorbate and carotenoids (Abebe et al ). The latter can absorb light energy for photosynthesis, protect plants from light‐induced oxidative damage and dissipate excess light energy through the reversible conversion of violaxanthin to zeaxanthin via the xanthophyll cycle.…”
Section: Ecological and Physiological Implicationsmentioning
confidence: 99%
“…Compared with the flag leaf, the genes for photosynthesis were preferentially expressed in the lemma and the palea of barley (Abebe et al ). Specifically, genes for the light reaction, the Calvin‐Benson cycle and the synthesis of light‐harvesting pigments were preferentially expressed in awns with a higher photosynthetic rate than those found in other organs of the ear (Abebe et al ). Similarly, in rice, the expression of genes and proteins responsible for glume photosynthesis, carbohydrate metabolism and resistance to abiotic stresses was upregulated by a pattern of water management (moderate wetting and drying irrigation) after anthesis; thus, the grain‐filling rate and the grain mass of inferior spikelets increased significantly (Chen et al ).…”
Section: Introductionmentioning
confidence: 99%